Wednesday

April 23, 2014

April 23, 2014

Posted by **missfubu-c** on Saturday, October 13, 2012 at 10:18pm.

(a)F(5t)=

(b)F(6t)=

- math -
**Reiny**, Sunday, October 14, 2012 at 12:32ama)

if f(x) = x^2 - 25t

f(5t) = (5t)^2 - 25t = 25t^2 - 25t

so the second one in the same way.

Notice we had a function of x, that is, f(x)

so only the terms that contain x's are affected in the substitution, unless you have a typo.

**Related Questions**

Math - How will I work this problem? Find the functional values requested in the...

Math - Find the functional values requested in the problem; h(x)=5x-4 (a) h(0...

ALGEBRA - Find the functional values requested in the problem. h(x)=3 x-1 (a) h(...

ALGEBRA - Find the functional values requested in the problem. h(x)=5 x-1

MATH - Assume f(x) = x2 + 4. Find the functional value requested. f(-6) =

Math - Assume f(x) = x2 + 3. Find the functional value requested. f(-5) =

ALGEBRA - Assume f(x) = x2 + 3. Find the functional value requested. f(-7) =

ALGEBRA - Assume f(x) = x2 + 3. Find the functional value requested. f(-7)

ALGEBRA - Assume f(x) = x2 + 4. Find the functional value requested. f(-3) =

math - If f(x) = 3x – 10, find the element of the domain associated with each of...